FIRST FORMS AND PROGRESS OF UZBEK FOLK PROVERBS - Bozorova Nasiba Pulotjonovna (Journals Park Publishing, 2022)
The article talks about the first forms of Uzbek folk proverbs and their improvement. Also, the use of proverbs on the inscription stones of Orhun Enasoy, their importance and artistic nature in the memoir will be discussed. The influence of society and time on the development of folk proverbs is studied.
Keywords: epitaph, proverb, study, stability, local historian, folk art, evolution, Yiaris, tabgach.